2007
DOI: 10.1038/nn1885
|View full text |Cite
|
Sign up to set email alerts
|

Non–cell autonomous effect of glia on motor neurons in an embryonic stem cell–based ALS model

Abstract: Here we report an in vitro model system for studying the molecular and cellular mechanisms that underlie the neurodegenerative disease amyotrophic lateral sclerosis (ALS). Embryonic stem cells (ESCs) derived from mice carrying normal or mutant transgenic alleles of the human SOD1 gene were used to generate motor neurons by in vitro differentiation. These motor neurons could be maintained in long-term coculture either with additional cells that arose during differentiation or with primary glial cells. Motor neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

47
541
2
10

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 727 publications
(606 citation statements)
references
References 33 publications
47
541
2
10
Order By: Relevance
“…Importantly, reduction of mSOD1 restricted to astrocytes slowed disease progression, in a similar manner as with microglial restricted mSOD1 reduction, likely attributed to inhibition of microglial activation 64. In fact, conditioned media from mSOD1 astrocytes is toxic to motor neurons in vitro 65. In vivo , astrocytes may mediate a neurotoxic environment because of their lowered expression of EAAT2 (or GLT‐1 in mice), a glutamate transporter able to clear glutamate surplus in the synaptic space 66, 67.…”
Section: Status Of Neuroinflammation In Als and Smamentioning
confidence: 77%
“…Importantly, reduction of mSOD1 restricted to astrocytes slowed disease progression, in a similar manner as with microglial restricted mSOD1 reduction, likely attributed to inhibition of microglial activation 64. In fact, conditioned media from mSOD1 astrocytes is toxic to motor neurons in vitro 65. In vivo , astrocytes may mediate a neurotoxic environment because of their lowered expression of EAAT2 (or GLT‐1 in mice), a glutamate transporter able to clear glutamate surplus in the synaptic space 66, 67.…”
Section: Status Of Neuroinflammation In Als and Smamentioning
confidence: 77%
“…Much of our understanding of the underlying mechanisms comes from studies of transgenic mice overexpressing toxic mutant forms of SOD1 (Cu, Zn-superoxide dismutase-1), which cause ALS in a subset of patients with a familial form of the disease. Mutant SOD1 triggers neurodegeneration in a cell-autonomous fashion in motor neurons, but also drives disease progression through non-autonomous mechanisms involving microglia and astrocytes [20][21][22]. Three death receptors -TNFα, p75 NTR and Fas/CD95 -have been implicated in cell autonomous and/or non-autonomous aspects of the disease.…”
Section: Involvement Of Death Receptors In Disease Mechanism and Thermentioning
confidence: 99%
“…In amyotrophic lateral sclerosis (ALS), it has recently been demonstrated that motoneuronal death is closely linked to impaired glial activity and excitotoxic extracellular environment (Di Giorgio FP et al, 2007;Nagai et al, 2007). Recent evidence points to BBB disruption (Garbuzova-Davis et al, 2007a;Zhong et al, 2008) as an early hallmark in the ALS animal model.…”
mentioning
confidence: 99%